Automated router configuration using JAVA-PHP programs / Noorul Asilah Osman - Osman, Noorul Asilah (2016)
Java-PHP Automated Router Configuration is a system application that allows users to automatically generate scripting configuration especially for Internet Protocol (IP) Core services more quickly and accurately. With this application system, validation, verification, design and profiling information will be carried out easily without using the traditional method of using Excel file to manually extract the router configuration. Aside to that, scripting can be automatically generated and clearly displayed. Currently the process is based on manually scripting in Excel for configuration and users are required to enter the profile information. The problem come due to the process takes longer time for each department to complete their own task due. Furthermore, certain department has to wait for other department to complete its task before other department can proceed. Due to. this problem, the initiatives is to build an application that will assist network engineers and administrator to configure IP core based services by automatically generating configuration scriptures and focusing more on the verification. It will push configuration scripting's in router automatically from the IP Core router. Therefore, it is essential that a program is written to organize these bulks of data for storage and data retrieval, by the entire related department in Telekom Malaysia (TM). The main specific goal of this study is to build an application that will assist network engineers and other administrators to configure Ethernet services automatically. It will generate configuration scriptures from the network system used; in this case IP Core network based equipment (router). This project also demonstrates the effectiveness of using an object oriented approach to analyze, design and programming. This system is developed by using several programming languages such as Virtual Basic, PHP and Java for Web Application. The outcome for this project is an automated router configuration which is one of the platforms by doing another automated task in our division to achieve all the objective as mention below to increase the productivity and revenue in TM.